Assessment of the determinants of pharmacy-based immunization prior to its utilization in Manila - Cortes, Ma. Elaine D.​; Silo, Marie Kyla Louise D.​; Sales, Jaybie A.​; Gloria, Mac Ardy J.​ (​​​​​​​​​​Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2017)
Immunizations are crucial to protecting patients from developing and dying from vaccine- preventable diseases (Terrie, 2016). In the Philippines, the administration of adult vaccine is now approved as an additional scope of the pharmacy practice in the recently passed New Pharmacy Law RA 10918 N Section IV. In line with the preventive aspects of pharmaceutical care, the American Society of Health- System Pharmacists (ASHP) has established guidelines on the Pharmacists' Role in Immunization. Pharmacy-based immunization (PBI) would contribute to the effort by providing more accessible and cheaper immunization service. Thus, it is important to identify and evaluate the determinants of PBI prior to its utilization relative to the general public?s view about the immunization program itself and the expanded service of pharmacies in participation to immunization service.
The four determinants predisposing, enabling, need and knowledge and satisfaction that were evaluated were based on Andersen?s Behavioral Model of Health Services Utilization from the Acosta- Ramirez study. Each determinant variable were lifted from the International Pharmaceutical Federation (FIP). A descriptive cross-sectional research designs was employed in the study. The study population consisted of residents from the municipalities of each district in Manila. The municipalities taken are Tondo I/II (district 1/2), Quiapo (district 3), Sampaloc (district 4/6), Intramuros (district 5), Paco (district 5/6), and Pandacan (district 6). Through a multi-stage sampling design, a total of 210 respondents were computed from the study population.
A total of 210 (100%) questionnaires were completely answered by the respondents. Majority of the respondents were female (57%), between 18 ? 30 years in age (39%), single (53%), college graduate (25%), self-employed (46%), and earning a household net monthly income of less than 12,000 pesos monthly (51%). When asked whether they will support and avail the immunization given that it is available in their local pharmacies, 80% answered positively.
Results showed that the determinants of pharmacy of the utilization of pharmacy-based immunization as analyzed inferentially are, the enabling (p=0.0058) and knowledge and satisfaction (p=0.0160). The specific variable under the enabling determinant that is individually significant is cost (p=0.003). For the knowledge and satisfaction determinant, courtesy (p=0.019) showed to have an individual significant relationship to the utilization of pharmacy based immunization. Moreover, the respondents? decision of accepting pharmacy-based immunization is approximately 12 times more likely when the cost is acceptable and is 2 times more likely when the immunizer is kind and courteous.
In conclusion, cost of the immunization service and the courtesy of the immunizer are the determinants for better patient acceptance and increased utilization of PBI. However, it is recommended that more districts or barangays in Manila and more number of respondents be used in the study population to improve the inferential analysis and to increase significance of the results. Interviewing the respondents and presentation of immunization cards would render a more reliable result. For further researches with the same area of concern, we recommend to use the questionnaire that we have instrumentalized since it scored high in the cronbach-alpha analysis. Also, we recommend that FDA and PPha to conduct a seminar or an activity about PBI that involves the people in the community to increase awareness about the new service.
Available to the general public.
​​​​​​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, June 2017. ​
Keywords: Immunization